Influence of chemical etchings on surface properties, in-vitro degradation and ion releases of 316l stainless steel alloy for biomedical applications - Say, Y.; Aslan, N.; Alla, A. M. A.; Ozmen, H. (Elsevier Science Sa, 2023)
Different surface treatments are applied to improve the surface properties of metallic biomaterials. Chemical etching is one of the common techniques used for roughening the surface. In this regard, the effects of different chemical media on the surface roughness, degradation, and ion release of 316L SS steel were investigated in this study. The 316L SS steel was exposed to chemical etching in six different chemical media including HNO3, H2SO4, HCl, HClO4, NaOH and Na2CO, at four different concentrations (1, 2, 4, and 8 Molar), and at three immersion times (10, 60, and 180 min). SEM, EDS, and XRD analyses were used to examine the morphological and chemical impacts of chemical etching on sample surfaces, and roughness was measured on all sample sur-faces. The effect of surface treatment on the degradation and ion release of the samples was comparatively examined. Characterization analyses indicated that the HNO3, H2SO4, and HCl media did not cause a significant reaction on the surface of the 316L SS. On the other hand, different phases were observed on the sample surfaces exposed to HClO4, NaOH, and Na2CO3 media. It was determined that the roughness had no linear correlation with the concentration and immersion time, and similarly, the degree of degradation and amount of ion release displayed no change depending on the roughness. Samples etched in H2SO4, HClO4, NaOH and Na2CO3 provided the highest roughness. It was found that H2SO4 caused a significant increase in the amount of ion release.
Keywords: 316L; Surface roughness; Degradation; Ion-release